Endoscopic transsphenoidal resection of craniopharyngioma - Liew, Kong Yew; Narayanan, Prepageran; Waran, Vicknes (Thieme Medical Publishers, 2018)
Objectives: To demonstrate, step-by-step, the technique and efficacy of endoscopic transsphenoidal approach in resection of a suprasellar craniopharyngioma. Design The video shows a step-by-step approach to the resection, covering the exposure, access, resection, and confirmation of resection and reconstruction. Setting: The surgery was performed in the University of Malaya Medical Centre, a tertiary referral center in the capital of Malaysia. Participants Surgery was performed jointly by Professor Prepageran from the department of otorhinolaryngology and Professor Vicknes Waran from the division of neurosurgery. Both surgeons are from the University of Malaya. Video compilation, editing, and voice narration was done by Dr. Kong Yew Liew. Main Outcome Measures: Completeness of resection and avoidance of intra- and postoperative complications. Results: Based on intraoperative views and MRI findings, the tumor was completely resected with the patient suffering only transient diabetes insipidus. Conclusion: Central suprasellar tumors can be removed completely via an endoscopic transsphenoidal approach with minimal morbidity to the patient.